Engineering Hydraulics: The Delhi Sultanate's Development of Irrigation Techniques and Water Management Systems - Khalid Bashir; Ishfaq Ahmad Mir; Irshad Ahmad Lone (Bulletin of Engineering Science, Technology and Industry, 2025)
India saw tremendous socioeconomic change under the Delhi Sultanate (1206–1526 CE), which was characterized by important developments in irrigation and water management systems. The agrarian economy that formed the foundation of the Sultanate's fiscal system depended heavily on these processes, which are still little understood in historical research. In order to overcome a variety of climatic obstacles, the kings used creative hydraulic engineering techniques, such as building wells, tanks, and canals and incorporating water technology from Central Asia and Persia. The present research looks at the Delhi Sultanate's many contributions to water management, including the technical aspects of their irrigation systems, their socio-political ramifications, and their lasting influence on the sociocultural and agricultural landscapes of the Indian subcontinent. The study intends to provide a comprehensive knowledge of how these hydraulic innovations affected agricultural production, income creation, and community involvement during this pivotal time through this approach.